Royally wronged : the Royal Society of Canada and Indigenous peoples - Backhouse, Constance, 1952-; Milton, Cynthia E.; Kovach, Margaret, 1964-; Perry, Adele (McGill-Queen's University Press, 2021)
"The Royal Society of Canada's mandate is to elect to its membership leading scholars in the arts, humanities, social sciences, and sciences, lending its seal of excellence to those who advance artistic and intellectual knowledge in Canada. Duncan Campbell Scott, one of the architects of the Indian residential school system in Canada, served as the society's president and dominated its activities; many other members - historically overwhelmingly white men - helped shape knowledge systems rooted in colonialism that have proven catastrophic for Indigenous communities. Written primarily by current Royal Society of Canada members, these essays explore the historical contribution of the RSC and of Canadian scholars to the production of ideas and policies that shored up white settler privilege, underpinning the disastrous interaction between Indigenous peoples and white settlers. Historical essays focus on the period from the RSC's founding in 1882 to the mid-twentieth century; later chapters bring the discussion to the present, documenting the first steps taken to change damaging patterns and challenging the society and Canadian scholars to make substantial strides toward a better future. The highly educated in Canadian society were not just bystanders: they deployed their knowledge and skills to abet colonialism. This volume dives deep into the RSC's history to learn why academia has more often been an aid to colonialism than a force against it. Royally Wronged poses difficult questions about what is required - for individual academics, fields of study, and the RSC - to move meaningfully toward reconciliation."--